The Establishment of The Kurdish National Council - Mahmoud Ahmed Alarabo (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The establishment of the Kurdish National Council was the prominent event of the Historic movement for the Kurds in Syria. That has been gathered all the Kurdish fractions under one umbrella، unified their political stance and their legal National demands in Syria. Which is the recognition of Kurds in the permanent Constitution of Syria، and removing all the racism projects against Kurds، removed its effects and compensate the affected people; as well as considering the Kurdish language as the second official language in the country. Syria demanded a federal pluralistic democratic republican state، and for the Kurds granted their own unified region. The Kurds and for the first time، were able to meet formally with the official Arab opposition when the Kurdish National Council joined the National Coalition of opposition forces and the Syrian Revolution and for the first time they recognized the existence of the Kurdish question in Syria and the need to be tackled in justice peacefully. The Kurds were able to participate and through Kurdish National Council to take part in Geneva negotiations through Syrian opposition coalition delegation، and therefore، for the first time the Kurds involved to discuss their country's future in an international conference seeking at the future of Syria. Kurdish National Council was able to aptly represent the Kurds in international forums as the legitimate representative of the Syrian Kurds، and won the recognition from local، regional and international powers. The Kurdish National Council turned to symbol of existence of the Kurdish issue and its address in Syria، as the legitimate representative of this issue.